MINERAL ASSEMBLAGES AND composition of ACCESSORY MAGNETITE OF THE VISHNEVOGORSKY ALKALINE COMPLEX (SOUTH URALS) - V.A. Popov; V.I. Popova; I.A. Blinov (Минералогия, 2017)
Accessory magnetite is a common mineral of rocks of the Vishnevogorsky alkaline complex, South Urals. Inclusions of ilmenite, pyrophanite and gahnite in magnetite are the exsolution products. Individuals of magnetite are characterized by compromise growth surfaces with potassium feldspar, albite, nepheline, annite, aegirine, cancrinite, analcime, zircon, calcite, pyrochlore, ilmenite, pyrite, pyrrhotite, sphalerite, apatite, pyrophanite, gahnite and calcioburbankite. The assemblages of magnetite in different rocks are eutectic. In most cases, magnetite contains low contents of Ti, Mn, Zn, Al (exsolution products) and V.